Valuation date seed waste meal as partial supplementation with corn yellow in pullet diets - Abdulruhman Belkaseem Alnakaa (Bani Waleed University Journal of Humanities and Applied Sciences, 2024)
The study's objectives were to determine the date seed waste meal's (DSWM) nutritional value, examine the fatty acid and amino acid profiles of the material, and gauge how easily amino acids could be digested (Experimental 1). In Experiment 2, the small intestines of chicks given DSWM as their main source of energy were examined histopathologically. Experimental 3 investigated the impact of different levels (0%, 7.5%, and 15%) of DSWM in poultry diets on digestibility. Results revealed that DSWM contains 96.33% dry matter, 7.2% crude protein, 8.9% ether extract, 3.61% crude ash, and 10.61% crude fiber, with 42.79% neutral detergent fiber, 20.83% acid detergent fiber, and 21.96% hemicellulose. DSWM also contains 69.62% nitrogen-free extract. The main fatty acids in DSWM were oleic acid (33.2%), linoleic acid (29.1%), palmitic acid (12.34%), and lauric acid (11.2%). Saturated fatty acids, monounsaturated fatty acids, and polyunsaturated fatty acids ranged from 27.0-44.3%, 41.45-49.2%, and 14.0-21.8%, respectively. Total sulfur amino acids in DSWM were 0.05% methionine, 0.13% cystine, 0.32% lysine, 0.73% arginine, 0.19% threonine, and 0.07% tryptophan. Phytase supplementation mitigated the negative impact of DSWM on amino acid digestibility. Histopathological examination revealed adverse effects of DSWM on the intestinal structure, particularly in the ileum and jejunum, with less impact on the colon. Amino acid supplementation decreased apparent metabolizable energy compared to other dietary additives and crumble treatments. Phytase consistently improved ash retention in diets with 7.5% and 15% DSWM. The effects of multienzymes, amino acids, and crumble varied based on the DSWM level, with crumble showing a decreasing effect as DSWM level increased (18.9% vs. 8.4%).